Concrete degradation by the formation of biogenic sulfuric acid in a Sewage Pumping Station - de Andrade Coni, Gabriella; Tafuri Costa, Amanda; Gonçalves Costa, Adriana; Sakuma, Guilherme (Revista ALCONPAT, 2022)
This work presents the study carried out in a Sewage Pumping Station after severe degradation was observed. The attack by biogenic sulfuric acid in sanitary sewage systems is widely studied in the literature, however, data on real work situations are still quite limited. Analyzes of the concentration of H2S in the air, carbonation depth, compressive strength test, petrography, SEM/EDS, XRD and chemical determinations were carried out in concrete cores extracted above the effluent level. The products identified on the surface were Gypsum, Jarosite, Ferrous Hydroxide, Ferrous Chloride and possibly Hisingerite. The results demonstrate the presence on the surface of both products from the dissolution of cement paste and 16 mm steel bars located in the attacked region.